2009
DOI: 10.21002/jepi.v9i2.165
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Macroeconomic Indicators to Foreign Investment in Indonesia

Abstract: This paper studies the effect of domestic and foreign macroeconomy performances on the foreign direct investment (PMA) in Indonesia, employing descriptive and inferencial (econometric model) analyses. The national economic growth and national interest rate affect significantly PMA in Indonesia. While the national inflation rate positively -effected on PMA, but results show that hyperinflation contributes to decreasing PMA. The macroeconomic improvement in some _competitor countries, especially Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, the theory of investment can refer to Krugman, Obstfeld, & Melitz (2014). Juanda & Mahyuddin (2009) and Gürsoy, Sekreter, & Kalyoncu (2013) examined the impact of economic growth on FDI. Juanda & Mahyuddin (2009) found that economic growth both in the domestic economy and foreign economy can promote FDI inflows in Indonesia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the theory of investment can refer to Krugman, Obstfeld, & Melitz (2014). Juanda & Mahyuddin (2009) and Gürsoy, Sekreter, & Kalyoncu (2013) examined the impact of economic growth on FDI. Juanda & Mahyuddin (2009) found that economic growth both in the domestic economy and foreign economy can promote FDI inflows in Indonesia.…”
mentioning
confidence: 99%
“…Juanda & Mahyuddin (2009) and Gürsoy, Sekreter, & Kalyoncu (2013) examined the impact of economic growth on FDI. Juanda & Mahyuddin (2009) found that economic growth both in the domestic economy and foreign economy can promote FDI inflows in Indonesia. Furthermore, Gürsoy, Sekreter, & Kalyoncu (2013) explained that FDI had a causal relationship with economic growth.…”
mentioning
confidence: 99%
“…As seen in the above equation, lags must be maintained for the ARDL model procedure. Juanda (2009) defined lag as the amount of time needed for a response (Y) to occur as a result of an impact (activity or decision). The Schwarz-Bayesian Criteria (SBC), Akaike Information Criteria (AIC), or any additional data criteria can pick the appropriate lag for the model; a successful model has the smallest value of whatever information criteria.…”
Section: Autoregressive Distributed Lag (Ardl)mentioning
confidence: 99%
“…(2) it provides complete, efficient information, high variability, more degrees of freedom, and reduced collinearity between variables; (3) it identifies and calculates results that are not identified by time series or cross-sections; and ( 4) it has the ability to more deeply examine dynamic problems that are more complex than those identified by time series or cross-sections. The panel analysis model was used to show the influence of the tourism sector and the threat of disaster on economic vulnerability [24], as follows:…”
Section: Search Radius 12mentioning
confidence: 99%